Pengaruh Kualitas Produk, Persepsi Harga, dan Citra Merek Terhadap Minat Beli: Studi Kasus pada Smartphone I Phone di Kota Bogor - Mahali, Jalaludin Al (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The purpose of this study was to analyze the effect of product quality, price perception, and brand image on purchase intention. Case Study on I Phone Smartphone in Bogor City. The influence of product quality, price perception, and brand image have an important role in creating buying interest. The purpose of this study was (1) to determine the effect of product quality on consumer buying interest on I Phone smartphones. (2) To determine the effect of price perception on consumer buying interest in I Phone smartphones. (3) To determine the effect of brand image on consumer buying interest on I Phone smartphones. (4) To determine the effect of product quality, price perception, and brand image together have an effect on consumer buying interest in I Phone smartphones. The number of respondents in this study were 200 respondents, taken from those who know I Phone Smartphones, both those who have never bought or who have bought and are domiciled in the city of Bogor. The research data was processed using SPSS version 22 . The results of this study are as follows: (1) Product Quality (X1) partially affects Purchase Interest (Y) with a t-count value greater than t-table (2.063 >1.972), thus H0 is rejected and H1 is accepted; (2) Price Perception (X2) partially affects Purchase Interest (Y) with t-count value greater than t-table (2.292 > 1.972), thus H0 is rejected and H2 is accepted; (3) Brand Image partially affects Purchase Interest (Y) with a t value greater than t table (11,154 > 1,972), thus H0 is rejected and H3 is accepted; Product Quality, Price Perception, and Brand Image simultaneously have a positive and significant effect on Purchase Interest with the calculated F value greater than F table (296,158 > 2.65), thus H0 is rejected and H4 is accepted. So it can be said that in this study the variables of Product Quality, Price Perception, and Brand Image play a role or contribute to Purchase Interest with an R-Square Value of 81.9%, while the rest is provided by other variables. Keywords: Product Quality, Price Perception, Brand Image, Buying Interest